Green Synthesis of Ag NPs Using Ustilago maydis as Reducing and Stabilizing Agent. (19th July 2022) - Cortés-Camargo, Stefani; Jiménez-Rosales, Angélica; Acuña-Avila, Pedro Estanislao
Abstract : Ustilago maydis (UM) is a fungus that grows naturally on Zea mays ; it reduces the corn yields, and thus, it represents huge economic loss; however, it can be used as an exotic food, and in the present work, it is successfully used as a reducing and stabilizing agent for the preparation of silver nanoparticles (Ag NPs) due to its content of amino acids and biosurfactants. The effects of the concentration of UM aqueous extract, pH, and sunlight on the particle size, surface plasmon resonance, stability, and morphology of Ag NPs obtained by green synthesis were evaluated. A green reduction was observed only in presence of UM, and colloidal Ag NPs were obtained with or without the presence of sunlight; nevertheless, continuous sunlight exposure greatly increased the reaction rate. Ag NPs tend to increase in size from 153 nm to 1400 nm at a higher pH and a greater amount of UM, and also, UM tends to stabilize the Ag NPs preventing their agglomeration according to measurement of zeta potential (−10.75 ± 0.84 mV) and SEM observation; furthermore, surface plasmon resonances were more intense between 400 and 480 nm of wavelength adding greater amount of UM. This study concludes that UM not only reduces AgNO3 but also acts as stabilizer of Ag NPs.